A Cross-Sectional Survey Study on Causes and Prevention of Badminton-Related Injuries Among College Students - De, Wanjun; Jin, Bingyu (Pacific International Journal, 2025)
Badminton is widely practiced among university students in China and provides substantial benefits for physical fitness, coordination, and social interaction, yet its high-intensity movements—including rapid direction changes and repetitive overhead strokes—also increase the risk of sport-related injuries. This study investigated the prevalence, causes, mechanisms, and preventive practices related to badminton injuries among students at XX College, Hohhot, Inner Mongolia, China. Using a cross-sectional survey design, 200 regular badminton participants completed a structured questionnaire covering demographic information, training habits, warm-up and prevention behaviors, injury history, perceived risk factors, and injury-prevention knowledge. Descriptive statistical analysis revealed a high prevalence of lower-limb injuries, particularly ankle sprains, muscle strains, and overuse conditions. Key contributing factors included inadequate warm-up, poor technique, fatigue, and inappropriate footwear, while students identified warm-up routines, strengthening exercises, and improved technique as important but insufficiently implemented prevention strategies. Many participants expressed the need for more formal education on injury prevention. Overall, the findings indicate that badminton-related injuries among college students are common yet highly preventable, highlighting the importance of strengthening warm-up practices, improving technical guidance, addressing fatigue, and promoting proper footwear use within university physical education programs.